Stem Cell Therapy for Digestive Tract Diseases: Current State and Future Perspectives - Trébol López, Jacobo; Georgiev Hristov, Tihomir; García Arranz, Mariano; García Olmo, Damián (My University, 2010)
Diseases of the digestive tract are complex and encompass a broad spectrum of different pathogeneses (inflammatory, ischemic, neoplastic, and functional deficit). The digestive tract is not a sterile environment, and its organs are composed of tissues with different embryologic origin and different morphologic and functional complexity. As a consequence, the management of these diseases is often challenging. Stem cell (SC) therapy has yielded some promising results in preclinical studies, and, recently, some approaches have been tested clinically. Indeed, during the last 5 years, the number of clinical trials with SCs for treatment of digestive tract diseases has increased 10-fold. The most advanced programs involve liver failure, Crohn's disease, and fistulous disease and are now in phase III of development. If progress continues and the preliminary results are confirmed, SC therapy will become a clinical reality in the near future. In this review we examine the basic concepts of the SC therapy, analyze the potential benefits of SCs in diseases of the digestive tract, and summarize current experience in the field and the future perspectives.